Exophiala Keratitis following Descemet Stripping Automated Endothelial Keratoplasty - Marta, Ana (Case Rep Ophthalmol Med, 2020)
PURPOSE: To report a case with Exophiala spp. keratitis in a Portuguese patient. METHODS: A case report with deep corneal brown-pigmented infiltrates that developed 2 months after a Descemet Stripping Automated Endothelial Keratoplasty (DSAEK) for pseudophakic bullous keratopathy. RESULTS: Diagnosis was established by positive direct examination and cultures from the surgically obtained corneal button. Slit-lamp images and anterior segment optical coherence tomography (AS-OCT) scans were obtained. CONCLUSION: This is the first described case of fungal keratitis caused by Exophiala spp. in Portugal and, to our knowledge, the first case following DSAEK in the literature.